Minimally invasive reduction of thoracolumbar burst fracture using monoaxial percutaneous pedicle screws: Surgical technique and report of radiological outcome. (24th December 2019) - Chung, Weng Hong; Eu, Wei Cheong; Chiu, Chee Kidd; Chan, Chris Yin Wei; Kwan, Mun Keong
Purpose: To describe the reduction technique of thoracolumbar burst fracture using percutaneous monoaxial screws and its radiological outcomes compared to polyaxial screws. Methods: All surgeries were performed by minimally invasive technique with either percutaneous monoaxial or percutaneous polyaxial screws inserted at adjacent fracture levels perpendicular to both superior end plates. Fracture reduction is achieved with adequate rod contouring and distraction maneuver. Radiological parameters were measured during preoperation, postoperation, and follow-up. Results: A total of 21 patients were included. Eleven patients were performed with monoaxial pedicle screws and 10 patients performed with polyaxial pedicle screws. Based on AO thoracolumbar classification system, 10 patients in the monoaxial group had A3 fracture type and 1 had A4. In the polyaxial group, six patients had A3 and four patients had A4. Total correction of anterior vertebral height (AVH) ratio was 0.30 ± 0.10 and 0.08 ± 0.07 in monoaxial and polyaxial groups, respectively ( p < 0.001). Total correction of posterior vertebral height (PVH) ratio was 0.11 ± 0.05 and 0.02 ± 0.02 in monoaxial and polyaxial groups, respectively ( p < 0.001). Monoaxial group achieved more correction of 13° (62.6%) in local kyphotic angle compared to 8.2° (48.0%) in polyaxial group. Similarly, in regional kyphotic angle, 16.5° (103.1%) in the monoaxial group and 8.1° (76.4%) in the polyaxial group were achieved. Conclusions: Monoaxial percutaneous pedicle screws inserted at adjacent fracture levels provided significantly better fracture reduction compared to polyaxial screws in thoracolumbar fractures.